KETAHANAN 45 JENIS KAYU INDONESIA TERHADAP RAYAP KAYU KERING DAN RAYAP TANAH - Mohammad Muslich; Sri Rulliaty (Jurnal Penelitian Hasil Hutan, 2016)
Natural durability of forty five wood species collected from several forest regions in Indonesia was tested against drywood termites (Cryptotermes cynocephalus Light.) and subterranean termites (Coptotermes curvignathus Holmgreen). Natural durability tests against dry-wood termites and subterranean termites were conducted based on Indonesian standard SNI 7207:2014. Results show that six wood species are classified as very durable wood (class I), eleven wood species are durable (class II), and 28 species belong to the low durability classes (class III, IV and V) against dry wood termites (C. cynocephalus Light.). Similar tests against substeranean termites (C. curvignathus Holmgreen) reveal that seven wood species are classified into highly resistant (durable class I), 14 wood species are resistant (durable class II), and the remaining 24 wood species belong to durability class of III, IV, and V. The testing results indicate that wood with high natural durability against dry wood termites is not necessarily resistant to subterranean termites and vice versa.